The Impact of Visionary Leadership, Teacher Competence, and Learning Innovation on Educational Quality: A Correlational Study of Private High School Teachers in Tangerang City - Muhammad Akbar; Yulita Pujilestari; Imas Masriah (Journal of World Science, 2026)
This study aims to determine the influence of Visionary Leadership, Teacher Competence, and Learning Innovation on Education Quality, both partially and simultaneously, in private high school teachers in Tangerang City. This study uses a quantitative approach with a correlational method. Data were collected through questionnaires distributed to 115 selected respondents using sampling techniques, then analyzed using analytical prerequisite tests (normality, homogeneity, and linearity) as well as simple and multiple linear regression analysis with the help of SPSS 25. The results showed that Visionary Leadership had a positive and significant effect on the Quality of Education (?yx1 = 0.703; count 9.761 > table 1.981), Teacher Competence had a positive and significant effect on the Quality of Education (?yx2 = 0.162; count 2.008 > table 1.981), and Learning Innovation had a positive and significant effect on the Quality of Education (?yx3 = 0.035; count 1.987 > table 1.981). Simultaneously, these three variables also have a significant effect on the Quality of Education with a Fcal value of 89.794 at a significance level of 0.000 < 0.05, forming a regression equation Y = 0.703X1 + 0.162X2 + 0.035X3. Visionary Leadership proved to be the most dominant variable that affects the Quality of Education compared to the other two variables. These findings confirm that improving the quality of education in private high schools will be more effective if it is focused on strengthening the visionary leadership of school principals, without neglecting teacher competency improvement and continuous learning innovation.